2002
DOI: 10.1161/hc0402.102863
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nuclear Factor-κB and Apoptosis Signal-Regulating Kinase 1 in G-Protein–Coupled Receptor Agonist–Induced Cardiomyocyte Hypertrophy

Abstract: These data indicate that GPCR agonist-induced cardiac hypertrophy is mediated through NF-kappaB activation via the generation of ROS. ASK1 is involved in GPCR agonist-induced NF-kappaB activation and resulting hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
273
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(290 citation statements)
references
References 19 publications
14
273
0
3
Order By: Relevance
“…This is consistent with an earlier study that showed that hyperglycemia itself enhances oxidative stress. 39 Oxidative stress, which is also activated by an AT 1 R-mediated pathway 40,41 and promotes myocardial fibrosis, 15,42 is likely to be involved in the development of myocardial fibrosis in DM, as shown in this study. Furthermore, we were able to show that there was a positive correlation between the extent of cardiac ACE expression and that of diastolic dysfunction.…”
Section: Impact Of Dm On Diastolic Dysfunction Myocardial Fibrosis Asupporting
confidence: 58%
“…This is consistent with an earlier study that showed that hyperglycemia itself enhances oxidative stress. 39 Oxidative stress, which is also activated by an AT 1 R-mediated pathway 40,41 and promotes myocardial fibrosis, 15,42 is likely to be involved in the development of myocardial fibrosis in DM, as shown in this study. Furthermore, we were able to show that there was a positive correlation between the extent of cardiac ACE expression and that of diastolic dysfunction.…”
Section: Impact Of Dm On Diastolic Dysfunction Myocardial Fibrosis Asupporting
confidence: 58%
“…Furthermore, the NF B dimer ratio has been shown to determine the ultimate level of target gene expression (18,22). NF B-mediated gene transcription has been proposed in models of myocardial diseases (3,77,78). Taken together with the previous finding that elevated levels of Myo/V1 are found in failing mammalian hearts (5,6), this study collectively suggests that Myo/V1 might play a significant NF B regulatory role at the transcriptional level during chronic pathophysiological conditions such as human heart failure.…”
Section: Figsupporting
confidence: 57%
“…Because in other studies interactions between GRK5 and NF-B signaling components (albeit at the protein level) have been demonstrated (14 -17), we looked for the potential of this system that can be activated by PKC to regulate GRK5 expression in myocytes. NF-B activation occurs through IB degradation and subsequent nuclear translocation of the p65 subunit to regulate gene transcription (9,32,33). NF-B has been implicated in cardiac hypertrophy, and the best evidence is from a transgenic mouse model with cardiac-specific expression of a mutant IB␣ that acts as a super-repressor of NF-B (30, 31).…”
Section: Discussionmentioning
confidence: 99%